Temporal-scale climate information and crop production management decisions: a case study in the North-Central region of Bangladesh - Mojid, Mohammad Abdul; Mousumi, Khadiza Akter; Kamal, Md Rowshon (Springer, 2024)
Shorter-period growth environment is more relevant to crop production management, especially during the weather-sensitive growth stages, compared to the integrated monthly or seasonal growth environment in areas with rapidly changing weather conditions. So, in addition to strategic planning, the short-period/tactical (≤ 10 days) planning of agriculture is also crucial for which tactical-scale hydro-climatic information is essential. This study investigated the major climate variables and reference evapotranspiration (ETo) of the past 30-year period (from 1990 to 2019) of the north-central region of Bangladesh on the 10-day and monthly resolutions, and identified the variation of the hydro-climatic variables on these temporal resolutions. The trends and associated shifts of the hydro-climatic variables were determined by the non-parametric Mann–Kendall test and Sen’s slope estimate, respectively. The wind speed and net radiation followed decreasing trend over time, while the temperature followed increasing trend, with a counter-balancing effect between these two sets of climatic forcing in controlling ETo. The effect of temperature on ETo was partially encountered through the deficit in saturation vapor pressure. The trends of the climate variables on the 10-day resolution were significantly (p ≤ 0.05) different compared to the monthly resolution, specifically in the main irrigation season, thus implying a rapidly changing weather conditions in the study region. The results demonstrate that any decisions on crop production management (e.g., irrigation scheduling and crop protection measures) based on climate variables of the monthly resolution will be erroneous; tactical-scale information–based decisions are essential.